2002
DOI: 10.1007/s00251-002-0445-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional analysis of the allelic polymorphism in the transcription regulatory region of interleukin-1α

Abstract: A strong correlation between the TT(-889) genotype over CC(-889) of the interleukin-1 alpha (IL-1 alpha) transcription regulatory region and age of Alzheimer's disease onset has recently been reported. To determine the functional effects of the genetic variants on plasma protein levels, we cloned the promoter region and determined its activity. The TT genotype significantly increased the transcriptional activity of the IL-1 alpha gene with respect to the CC genotype. A slight increase of the IL-1 alpha mRNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
132
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(138 citation statements)
references
References 15 publications
3
132
0
3
Order By: Relevance
“…Our study also shows that this SNP lies within a DNase cluster, which is commonly found to contain cis-regulatory elements such as enhancers, promoters and silencers [42], but these elements have not been demonstrated for this locus so far. It is in agreement with previous studies that found this SNP has regulatory properties on IL1A gene expression [44]. Patients with the IL1A T allele may have higher levels of IL-1α in circulation with more intense inflammatory response.…”
Section: Discussionsupporting
confidence: 82%
“…Our study also shows that this SNP lies within a DNase cluster, which is commonly found to contain cis-regulatory elements such as enhancers, promoters and silencers [42], but these elements have not been demonstrated for this locus so far. It is in agreement with previous studies that found this SNP has regulatory properties on IL1A gene expression [44]. Patients with the IL1A T allele may have higher levels of IL-1α in circulation with more intense inflammatory response.…”
Section: Discussionsupporting
confidence: 82%
“…Cytokines are crucial regulators to promote or suppress inflammation. Single nucleotide polymorphisms (SNPs) of inflammatory cytokines may change the transcription rate and consequently the production of cytokines (Dominici et al 2002, Wen et al 2006, Prasad et al 2010, and thus may modify individual susceptibility to AITDs. Various cytokines and respective genetic polymorphisms have been reported to be associated with AITD, but the results are inconsistent (Chen et al 2005, Shiau et al 2006, Anvari et al 2010, Liu et al 2010, Yan et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Hence amongst the Swahili participants, the association between [rs1800587] IL-1A -889 and chronic periodontitis was similar to studies in Caucasians, probably reflecting that the genetic make-up is a mosaic with Caucasoid contribution. The increased destruction of the periodontium in those genotype-positive for IL-1A-889 allele1, are probably due to reduced production of IL-1α cytokine [30]. This leads to increased destruction of the periodontium due to low levels of IL-1α protein resulting in lowered recruitment of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to increased destruction of the periodontium due to low levels of IL-1α protein resulting in lowered recruitment of inflammatory cells. Variations in IL-1α also affect the production of IL-1β [30,31]. The distribution of allele 2 at IL-1A locus -889 in Swahili participants was 80.4% in cases and 92.9% in controls, OR=0.32, 95%CI=1.16 -0.61, p<0.001.…”
Section: Discussionmentioning
confidence: 99%